Human movement representation in virtual environment using gaming software - Shahrol, Mohamaddan; Syed Tarmizi, Syed Shazali; Ana Sakura, Zainal Abidin; Case, Keith (Penerbit UTM Press, 2015)
Human movement in crowd can be considered as complex and unpredictable. In this research, image analysis, video observation and conceptual behaviour was developed as a method to understand the human movement in crowd. Based on the method, human movement was represented or converted into the virtual environment using gaming software called DarkBASIC Professional (DBPro). The developed program using DBPro was applied as a tool to simulate and predict human movement in different building layout. Two subjects (adult and older people) were selected as the virtual entities. Human movement at the bottleneck and non-bottleneck layout was presented in this paper as example of case study.